Kajian Iklan Layanan Masyarakat Tentang Pentingnya Mengucapkan Terima Kasih Bagi Para Remaja Di Surabaya - Sugoto, Mella Christa; Dektisa H., Andrian; Cahyadi, Jacky (Institute of Research and Community Outreach - Petra Christian University, 2009)
This visual communication’s design is accomplished to improve society awareness on how importance of expressing thank you, especially for Surabaya’s adolescent. Background of this study is formed by attitude and character descent in our society. Expressing thank you should be a simple way but in fact this word is rarely heard, whereas appreciate for all services and helps we received is the important thing in our life. Methode that is used in this study is qualitative, means getting the result by looking data in field and analyzing then. From data which is get, our adolescents think that expressing thank you is not important to do. Because its include a social problem, so I hope a Public Service Ad could be a solution to solve its problem. This Public Service Ad will be using effective media in informing message and this design is aimed to make attitude alteration in our Indonesia society.